(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article scientifically studies the effect of athletics training on functional training in cadets of military educational institutions. The study involved 1-2 stage cadets who were separated into experimental and control groups. In the experimental group, athletics exercises (running different distances, interval loading, jumping exercises) were systematically introduced into the physical training process. The control group, on the other hand, operated on a traditional physical fitness program.